Hybrid Zigbee RFID model for tag detection and energy tradeoff. (23rd November 2020) - Bagirathi, S.; Sankar, Sharmila; Sandhya, M.
Active RFID systems are utilised widely in extensive applications and have limited radio communication. Collisions subsist during the tag detection process of the reader which cause lassitude of tag's battery life. Surmounting these collisions and incrementing tag identification rate with remarkable high throughput remains as a key challenge in RFID based applications. Zigbee network provides multi hop data transmission and covers long distances. In this paper we propose a hybrid Zigbee RFID system model implemented with dynamic frame slotted grouping collision resolution protocol. During every iteration of tag estimation the frame size is adjusted predicated on the comparison of total number of singleton and idle slots against the number of collision slots without eliminating idle slots. Simulations were performed utilising Opnet simulator which showed decreased collision rate, execution time, system overhead and amended performance in the metrics of tag identification rate, energy efficiency with a maximum throughput of 0.63.